2013
DOI: 10.1177/1553350613479178
|View full text |Cite
|
Sign up to set email alerts
|

Conversion From Cephalic Vein to External Jugular Vein

Abstract: Conversion to external jugular vein cut-down is safely and easily applied in cases of cephalic vein cut-down failure. This method did not take more time than the percutaneous subclavian method. However, placement of the port should be made more carefully to prevent angulation of the catheter. We provide an alternative method to deal with failure of cephalic vein cut-down.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…When the carboxyl CQO is hydrogen-bonded but not dimerized, as in alcohol-carbonyl bonding, the -COOH stretching band shifts to B1730 cm À1 . [44][45][46] The peak assignment is presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…When the carboxyl CQO is hydrogen-bonded but not dimerized, as in alcohol-carbonyl bonding, the -COOH stretching band shifts to B1730 cm À1 . [44][45][46] The peak assignment is presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…According to Wysiadecki et al [ 6 ] persistence of jugulocephalic vein increases the risk of complications during the clavicular fractures, cephalic vein catheterization, or head and neck surgery. Lin et al [ 14 ] recommend external jugular vein cut-down in cases of failure of cephalic vein cut-down procedures. Apart from the above said procedures, the persistence of jugulocephalic vein is of cosmetic concern also, and can be safely excised for the same reason [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the wide application of TIVAPs, there is no consensus whether one or the other access site of implantation for TIVAP is clinically superior. Although several studies that compared chest access and arm access had been reported by various institutions, some of the results are conflicting and within small population of patients 1416. In the present study, we attempted to investigate and assemble the most comprehensive clinical data currently available in the literature to address a debatable issue: which approach, the arm port or the chest port, is more clinically beneficial to oncologic patients for the implantation of TIVAPs?…”
Section: Introductionmentioning
confidence: 99%